Interhemispheric white matter integrity in young people with bipolar disorder and at high genetic risk. Issue 11 (13th June 2016) - Roberts, G.; Wen, W.; Frankland, A.; Perich, T.; Holmes-Preston, E.; Levy, F.; Lenroot, R. K.; Hadzi-Pavlovic, D.; Nurnberger, J. I.; Breakspear, M.; Mitchell, P. B.
Abstract : Background: White matter (WM) impairments have been reported in patients with bipolar disorder (BD) and those at high familial risk of developing BD. However, the distribution of these impairments has not been well characterized. Few studies have examined WM integrity in young people early in the course of illness and in individuals at familial risk who have not yet passed the peak age of onset. Method: WM integrity was examined in 63 BD subjects, 150 high-risk (HR) individuals and 111 participants with no family history of mental illness (CON). All subjects were aged 12 to 30 years. Results: This young BD group had significantly lower fractional anisotropy within the genu of the corpus callosum (CC) compared with the CON and HR groups. Moreover, the abnormality in the genu of the CC was also present in HR participants with recurrent major depressive disorder (MDD) ( n = 16) compared with CON participants. Conclusions: Our findings provide important validation of interhemispheric abnormalities in BD patients. The novel finding in HR subjects with recurrent MDD – a group at particular risk of future hypo/manic episodes – suggests that this may potentially represent a trait marker for BD, though this will need to be confirmed in longitudinal follow-up studies.